Field Experiments in Religion: A Dream Whose Time Has Come - Wright, Bradley R. Enter (Journal for the scientific study of religion, 2018)
Field experiments offer powerful tests of causality in real-world settings. They have high validity-both internal and external-and require smaller inferential leaps than observational or laboratory methods. Nonetheless, they are rarely applied to religion. This article advocates for the frequent use of field experiments in the study of religion. It reviews their methodological advantages, and it identifies various ways that religion can be incorporated into a field experiment design. It proposes multiple strategies for creating feasible, ethical religion field experiments as well as optimizing them. Ultimately, field experiments have the potential to transform the study of religion.